On the Practice of Lagging Variables to Avoid Simultaneity - Reed, William Robert (Oxford bulletin of economics and statistics, 2015)
A common practice in applied economics research consists of replacing a suspected simultaneously determined explanatory variable with its lagged value. This note demonstrates that this practice does not enable one to avoid simultaneity bias. The associated estimates are still inconsistent, and hypothesis testing is invalid. An alternative is to use lagged values of the endogenous variable in instrumental variable estimation. However, this is only an effective estimation strategy if the lagged values do not themselves belong in the respective estimating equation, and if they are sufficiently correlated with the simultaneously determined explanatory variable.